PENERAPAN PENDEKATAN SETS (SCIENCE ENVIRONMENT TECHNOLOGY SOCIETY) PADA PEMBELAJARAN REAKSI REDUKSI OKSIDASI - Aan Hasanah; Mahdian Mahdian (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2013)
This research aims to find out : (1) cognitive differences in learning outcomes between students who are learning to use the SETS approach (Science, Environment, Technology, and Society) and students learn using conventional learning material redox This study aims to find out, (2) student learning activities that use the SETS and conventional learning material redox reactions, and (3) students' response to the SETS approach. The research method is a quasi experimental design with nonequivalent control group design. The study population was a class X student of SMAN 12 Banjarmasin academic year 2011/2012. Sample was determined by purposive random sampling by 2 classes of 4 classes. Data collection technique used achievement test, questionnaire, observation and documentation. The technique of data analysis using t-test and descriptive analysis. The results showed that : (1) there are differences in cognitive learning outcomes between students who are learning to use the approach SETS and students who learn using conventional learning material redox reactions, (2) student learning activities that use the SETS more active than the student activity using conventional learning material redox reactions, (3) implementation of the approach SETS received a positive response from students. Key Words: SETS approach, cognitive learning outcomes,, oxidation reduction reaction.